2016
DOI: 10.1158/0008-5472.can-15-3451
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint Antibodies but not T Cell–Recruiting Diabodies Effectively Synergize with TIL-Inducing γ-Irradiation

Abstract: T cell-recruiting bispecific antibodies (bsAb) show promise in hematologic malignancies and are also being evaluated in solid tumors. In this study, we investigated whether T cell-recruiting bsAbs synergize with hypofractionated tumor radiotherapy (hRT) and/or blockade of the programmed death-1 (PD-1) immune checkpoint, both of which can increase tumor-infiltrating lymphocyte (TIL) numbers. Unexpectedly, large melanomas treated with hRT plus bsAb (AC133ÂCD3) relapsed faster than those treated with hRT alone, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 57 publications
6
59
0
Order By: Relevance
“…Later on, the amount of the cytotoxic T cells dropped again (32). Our data also reveal that CD8 + T cells do migrate in solid tumors that have been irradiated with a hypofractionated protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Later on, the amount of the cytotoxic T cells dropped again (32). Our data also reveal that CD8 + T cells do migrate in solid tumors that have been irradiated with a hypofractionated protocol.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that hRT can elevate CD8 þ tumorinfiltrating lymphocytes (TILs) between days 5 and 8 after hRT (20)(21)(22), which corresponds to the peak of the acute T-cell response against microbial antigens (23). Because T lymphocytes (including TILs) are usually regarded as highly radiosensitive (24,25), it is conceivable that hRT schedules extending into the period during which RT/ICB-induced T cells infiltrate the irradiated tumor might be less immunogenic than shorter schedules.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the cytotoxic T cells in the tumor was, however, limited since later on the amount of these adaptive immune cells dropped again. 134 In the CT26 colon cancer model in BAlb/c mice, we observed a peak of CD8+ T cells in the tumor 5 days after the last irradiation with 2×5 Gy at day zero and four. 90 From the clinical point of view, a re-irradiation on these days with higher single doses of RT should be counter-productive since the beneficial immune cells would be hit by the irradiation.…”
Section: Dynamics Of Immune Cell Infiltrationmentioning
confidence: 73%
“…Hettich and colleagues demonstrated that irradiation with 2×12 Gy on consecutive days of B16 melanoma tumors induces a high infiltration of CD8+ T cells at day 5 after the last irradiation. The presence of the cytotoxic T cells in the tumor was, however, limited since later on the amount of these adaptive immune cells dropped again . In the CT26 colon cancer model in BAlb/c mice, we observed a peak of CD8+ T cells in the tumor 5 days after the last irradiation with 2×5 Gy at day zero and four .…”
Section: Immunological Basis For Design Of Multimodal Radio‐immunothementioning
confidence: 78%